Closed reduction and minimally invasive screw osteosynthesis of Pipkin femoral head fractures - Kloub, Martin; Holub, Karel; Peml, Marek; Urban, Jiri; Latal, Pavel (Journal of applied biomedicine, 2023)
BACKGROUND: Femoral posterior hip dislocation with associated femoral head fractures (Pipkin fractures) are rare high-energy injuries. Published treatment modalities involve conservative treatment, head fragment resection, open reduction and internal fixation, and total hip replacement. The experience with mini-invasive screw osteosynthesis of these fractures is the main focus of our study. METHODS: Seven Pipkin fractures (five Pipkin II and two Pipkin I) in six patients were treated by closed reduction of hip dislocation, followed by minimal invasive lag screw osteosynthesis. Cancellous screw(s) were inserted from the incision on the lateral hip through the femoral neck to the reduced fracture fragment. In all patients, postoperative CT was performed to check the quality of surgery. Active physiotherapy with immediate toe-touch weight bearing was the routine postoperative protocol. In all patients, radiological and clinical results were evaluated with the Thompson Epstein, Merle d'Aubigne and Postel score, and Harris hip score. RESULTS: All fractures united, and all femoral heads survived. Infectious complications were not observed, and no secondary surgery was needed. After an average follow-up of 18.4 months, the average Merle d'Aubigne and Postel score was 17.7 points, while the mean Harris hip score reached 98.1 points. The majority of patients achieved an excellent Thompson-Epstein clinical and radiological outcome. All patients returned to their original occupation. CONCLUSIONS: Mini-invasive screw osteosynthesis can be used for the treatment of Pipkin type I-II femoral head fractures. Successful reduction of hip dislocation and head fracture is necessary for using this technique. Long-term follow-up is necessary to confirm this technique.
Keywords: luxace kyčle; kostní šrouby; Femur Head; Minimally invasive treatment; fraktury kyčle; hlavice femuru; Hip Fractures; Screw osteosynthesis; Bone Screws; Humans; Hip Dislocation; Femoral Fractures; Pipkin; lidé; fraktury femuru; Femoral head fracture